1998
DOI: 10.1021/bi980096y
|View full text |Cite
|
Sign up to set email alerts
|

Liposome−Cell Interactions in Vitro:  Effect of Liposome Surface Charge on the Binding and Endocytosis of Conventional and Sterically Stabilized Liposomes

Abstract: The cellular uptake of liposomes is generally believed to be mediated by adsorption of liposomes onto the cell surface and subsequent endocytosis. This report examines the effect of liposome surface charge on liposomal binding and endocytosis in two different cell lines: a human ovarian carcinoma cell line (HeLa) and a murine derived mononuclear macrophage cell line (J774). The large unilamellar liposomes were composed of 1, 2-dioleolyl-sn-glycero-3-phosphatidylcholine with and without the addition of either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
335
1
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(360 citation statements)
references
References 36 publications
18
335
1
6
Order By: Relevance
“…Even under extended incubation times, PRINT nanoparticles exhibited no cytotoxicity. Numerous studies have shown that surface charge has a significant impact on cellular internalization of a variety of nanocarriers (23). Dependence of surface charge on cellular internalization of PRINT nanoparticles was investigated by using rapidly internalized high-aspect-ratio cylindrical nanoparticles (d ϭ 150 nm, h ϭ 450 nm).…”
Section: Resultsmentioning
confidence: 99%
“…Even under extended incubation times, PRINT nanoparticles exhibited no cytotoxicity. Numerous studies have shown that surface charge has a significant impact on cellular internalization of a variety of nanocarriers (23). Dependence of surface charge on cellular internalization of PRINT nanoparticles was investigated by using rapidly internalized high-aspect-ratio cylindrical nanoparticles (d ϭ 150 nm, h ϭ 450 nm).…”
Section: Resultsmentioning
confidence: 99%
“…HeLa cells readily internalize nanoparticles of similar size to those used in this work, including 120 nm phospholipid vesicles, 50 nm gold nanoparticles and 18 nm silica nanoparticles. [35][36][37] Furthermore, EGFP fluorescence was stable within the cell in excess of two hours, suggesting that the PPN architecture protects the encapsulated components from intracellular proteases which may degrade the protein. Combined with PPN permeability and stability studies, these results strongly suggest the utility of polymerized PPNs for delivering enzymes and large molecular weight reporters to the intracellular environment and may represent a new paradigm for cellular analysis as well as diagnosis and treatment of disease.…”
Section: Resultsmentioning
confidence: 99%
“…For gene expression to occur, DNA plasmids enter the cell and its cell nucleus. Although there are three possible pathways of cell entry, endocytosis is likely the principal mechanism for transfection (Caplen et al, 1995;Lasic, 1998;Miller et al, 1998;Noguchi et al, 1998). After cellular uptake, the released cDNA is taken up by the nucleus (Felgner et al, 1995).…”
Section: Discussionmentioning
confidence: 99%